Plant growth‐promoting rhizobacteria: a novel management strategy for Meloidogyne incognita on turfgrass. Issue 9 (16th May 2020) - Groover, Will; Held, David; Lawrence, Kathy; Carson, Kendra
Abstract: BACKGROUND: Meloidogyne spp., root‐knot nematodes, are among the most economically important plant‐parasitic nematodes in turfgrass in the United States. Only a few nematicides are available or efficacious for plant‐parasitic nematodes in turfgrass in the United States, and recent work has demonstrated the potential for microbial control of root‐knot nematodes in field crops. The objectives of this study were to evaluate the efficacy of 104 plant growth‐promoting rhizobacteria (PGPR) strains isolated from grasses in Alabama against M. incognita in vitro, and their ability to manage plant‐parasitic nematodes in the glasshouse and microplot settings. RESULTS: In vitro mortality ranged from 0.9% to 94.6% by all PGPR strains screened. Ten individual PGPR strains and one three‐strain blend (a total of 13 PGPR strains) were advanced to glasshouse and microplot screening. In the glasshouse, six of the 11 PGPR treatments significantly reduced M. incognita population density, with a few strains also promoting some root growth. In the microplot, five of the 11 PGPR treatments significantly reduced M. incognita population density. CONCLUSION: Of these strains, 11 were identified as Bacillus spp., one as Stenotrophomonas rhizophila and one as Paenibacillus sonchi . Eight of these strains also were found to have nitrogenase activity, and seven had the ability to produce siderophores, showing a potential mechanism for growth promotion. Overall, results indicate that multiple strains of Bacillus spp. and one strain of S. rhizophila have the potential to reduce M. incognita population density and enhance turfgrass root growth. © 2020 Society of Chemical Industry Abstract : Evaluation of PGPR for root‐knot nematode suppression on turfgrass: in vitro tomicroplots